Oligodendrocyte degeneration and concomitant microglia activation directs peripheral immune cells into the forebrain. (June 2019) - Chrzanowski, Uta; Bhattarai, Sudip; Scheld, Miriam; Clarner, Tim; Fallier-Becker, Petra; Beyer, Cordian; Rohr, Sven Olaf; Schmitz, Christoph; Hochstrasser, Tanja; Schweiger, Felix; Amor, Sandra; Horn-Bochtler, Anja; et al.
Abstract: Brain-intrinsic degenerative cascades are a proposed factor driving inflammatory lesion formation in multiple sclerosis (MS) patients. We recently showed that encephalitogenic lymphocytes are recruited to the sites of active demyelination induced by cuprizone. Here, we investigated whether cuprizone-induced oligodendrocyte and myelin pathology is sufficient to trigger peripheral immune cell recruitment into the forebrain. We show that early cuprizone-induced white matter lesions display a striking similarity to early MS lesions, i.e., oligodendrocyte degeneration, microglia activation and absence of severe lymphocyte infiltration. Such early cuprizone lesions are sufficient to trigger peripheral immune cell recruitment secondary to subsequent EAE (experimental autoimmune encephalomyelitis) induction. The lesions are characterized by discontinuation of the perivascular glia limitans, focal axonal damage, and perivascular astrocyte pathology. Time course studies showed that the severity of cuprizone-induced lesions positively correlates with the extent of peripheral immune cell recruitment. Furthermore, results of genome-wide array analyses suggest that moesin is integral for early microglia activation in cuprizone and MS lesions. This study underpins the significance of brain-intrinsic degenerative cascades for immune cell recruitment and, in consequence, MS lesion formation. Highlights: Cuprizone-induced oligodendrocyte apoptosis triggers peripheral immune cell recruitment into the forebrain. Peripheral immune cell recruitment induces acute axonal injury. Moesin is expressed by microglia and immune cells.